Irrigation practices, water effectiveness and productivity measurement. (25th May 2019) - Chatzimichael, Konstantinos; Christopoulos, Dimitris; Stefanou, Spiro; Tzouvelekas, Vangelis
Abstract: This paper develops a consistent theoretical framework for measuring irrigation water effectiveness and its impact on productivity growth rates by assuming a smooth transition process from traditional to modern irrigation technologies among individual farmers. The econometric model is based on a two-stage estimation procedure incorporating the transition process within a primal TFP decomposition framework. An empirical investigation addresses a panel of 56 small-scale greenhouse farms in Crete, Greece during the 2010–2013 period. The results indicate that technical change driven by irrigation water technology improvement contributes significantly to total factor productivity growth. Further, the impacts of specific climatic and soil conditions do not allow farmers to fully explore the potential of the new irrigation technology delaying adoption rates.